Red's hot cowboy ebook - Brown, Carolyn (Spikes & Spurs, 2011)
Book 2 in the Spikes & Spurs Series He wasn't looking for trouble... But when the cops are knocking on your door, trouble's definitely found you. And this is where Wil Marshall finds himself after checking in to the Longhorn Inn. It could all be a big mistake, but Wil's not getting much sleep. Then the motel owner—who is drop dead gorgeous and feisty to boot—saves him from an even worse night behind bars. Now he owes her one, big time. ...But Trouble comes in all shapes and sizes Pearl never wanted that run-down motel, but her aunt didn't leave her much choice. And then this steaming hot cowboy shows up looking for a place to rest. Next thing she knows, she wants to offer him more than just room service. But if he calls her Red one more time, he won't be the only one accused of murder. Sparks are definitely flying and before long, the Do Not Disturb sign might be swinging from the door. Spikes & Spurs Series Love Drunk Cowboy (Book 1) Red's Hot Cowboy (Book 2) Darn Good Cowboy Christmas (Book 3) One Hot Cowboy Wedding (Book 4) Mistletoe Cowboy (Book 5) Just a Cowboy and His Baby (Book 6) Cowboy Seeks Bride (Book 7) Praise for Love Drunk Cowboy: "Brown revitalizes the Western romance with this fresh, funny, and sexy tale filled with likable, down-to-earth characters." —Booklist "Tender and passionate love scenes... endearing and quirky characters...What an absolutely adorable story." —The Romance Studio "Charming...full of sassy fun." —BookPage